Questions of perfection of the standard-legal base and guarantees in sphere of journalistic activity (Socially-legal and criminally-legal aspects) - Аліханов, Бобир Батирович; Лихова, Софія Яківна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Article is devoted to the research of legislative base of activity of mass-media in Uzbekistan. The comparative analysis of a criminal liability for the crimes connected with activity of mass-media is carriedout.